High tech counseling. - Hohenshil, Thomas H. (Journal of Counseling & Development)
An overview of the use of technology in counseling is presented. A review of four articles from the first issue of the entirely Internet-based Journal of Technology in Counseling dealing with computer-assisted simulation for counselor training, the use of technology for advocacy in school counseling, the use of technology in counseling assessment, and the use of videotaping in developmental supervision is presented, and the implications of these articles as well as recent technology-related developments by the Association for Counselor Education and Supervision and the American Counseling Association are considered.